Analisis Dampak Penggunaan Chatbot Ai Dalam Pembelajaran Di Kalangan Mahasiswa PGSD Universitas Jambi - Subron Hadid; Ulfa Ramadhani; Silvia Dian; Andi Gusmaulia Eka Putri (Sakura Digital Nusantara, 2024)
The rapid advancement of Artificial Intelligence (AI) technologies, particularly chatbots, has significantly impacted various aspects of education, including higher education. This study aims to evaluate the impact of AI chatbot utilization on learning among Elementary School Teacher Education (PGSD) students at the University of Jambi. Using a quantitative descriptive research design, data were collected from 100 randomly selected PGSD students through questionnaires, interviews, and observations. The findings indicate that AI chatbots enhance learning efficiency, provide personalized academic support, and increase learning motivation. However, challenges such as contextual understanding limitations and reduced human interaction were also identified. Recommendations include enhancing AI chatbot capabilities and balancing human-machine interactions to optimize educational effectiveness.